State of Apoptosis in Acute Epstein - Barr Virus Infection in Children - S.A. Kramarev; N.N. Taradiy; O.V. Vygovskaya (Zaslavsky O.Yu., 2013)
The paper presents an scientific review on the study of the question of apoptosis of immunocompetent cells in pathological processes, including at the Epstein - Barr virus infection. Also we present data of our own investigations which revealed a violation of the expression of markers of apoptosis of immunocompetent cells in children with acute Epstein - Barr virus infection. Fas/Apo-1 level exceeded the reference value of 2.9 times, Bcl-2 - 2.3 times, Bax - 3.2 times, INF-γ - 3.1 times, TNF-α - 3 times, annexin V - 2.5 times as compared with the comparison group.